Analysis of Zakat Literacy Level Measurement in the Community in Mukomuko Regency - Dais Farida; Iwan Setiadi; Edy Saputra; Mu'min Mutaqin (Badan Penerbit STIEPARI Press, 2025)
Until now, the majority of zakat associations in BAZNAS Mukomuko District are still focused on optimizing civil servants. Out of a total of 2062 muzzaki, 76% are civil servants, while only 24% come from the general public. The zakat collection is still relatively small, far from its full potential. Out of a potential of 10 billion, only Rp. 1,875,250,884 or approximately 18% has been collected. This is indicative of the lack of public literacy on zakat. Therefore, the objective of this research is to measure the level of zakat literacy among the residents of Mukomuko District, with a focus on the Muzakki of BAZNAS Mukomuko District. The research method employed is qualitative, and zakat literacy is analyzed using a test instrument measured using a multiple-choice method. The research findings indicate that the zakat literacy index in Mukomuko District falls into the 'moderate' category with a value of 78.7. The factors contributing to this level include knowledge, awareness, culture, spending priorities, lack of education, and educational factors.